PENGARUH SERVANT LEADERSHIP DAN BUDAYA KERJA TERHADAP QUALITY OF WORK LIFE SERTA DAMPAKNYA PADA KEPUASAN KERJA PEGAWAI(Studi Pada Dinas Perindustrian dan Perdagangan Kota Pasuruan) - Yanita Dwi Hartanti; Muryati Muryati (Bajang Institute, 2022)
This study aims to obtain empirical evidence of servant leadership abilities and work culture in encouraging increased job satisfaction, either directly or through the mediation of quality of work life.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 79 employees of the Industry and Trade Office of Pasuruan City.Empirical evidence shows that both servant leadership and work culture are not able to strongly encourage increased job satisfaction, but to the quality of work life both are strong enough. The role of quality of work life as a mediation is very strong, both in mediating the influence of servant leadership on job satisfaction and on the influence of work culture on job satisfaction. This finding is supported by the descriptions of the four variables, all of which received high responses, including indicators of vision and trust, values and beliefs, work integration, growth and development, co-workers, and supervisors.